Education quality and social justice in the global South : challenges for policy, practice, and research - Tikly, Leon.; Barrett, Angeline M. (Abingdon, Oxon : Routledge, 2013)
'Although more children than ever before are now enrolled in school, in the global South a good quality education remains out of reach for all except a privileged few. Most pupils experience inadequately prepared and poorly motivated teachers struggling to deliver new and complex curricula with insufficient learning resources in overcrowded classrooms, often using language that neither learners nor teachers speak outside school. For these learners, a good quality education must be a socially just education that is inclusive, relevant and democratic. It must develop the capabilities of learners to promote economic growth, create sustainable livelihoods, contribute to peaceful and democratic societies and achieve individual wellbeing. This in turn requires developing the professional capabilities of teachers and leaders.This book includes contributions from leading scholars in the field of education and development. It draws on state of the art evidence from the five year EdQual research programme on implementing education quality in low income countries and other relevant research. Through exploring recent initiatives in areas such as the curriculum, the use of ICTs, language and literacy, school effectiveness and leadership, the contributions go beyond looking at inputs and outputs for good quality education to open up the black box of the classroom and explore how practices of teaching and learning impact on different groups of learners. Some of the cross-cutting themes explored include defining quality, gender, inclusion, taking successful initiatives to scale and planning for both quality and equality. Education Quality and Social Justice in the Global South will appeal to undergraduate and postgraduate students and researchers within the fields of international and comparative education, teacher education, educational policy, poverty and development studies, African and Asian studies and related disciplines in the global North and South'--
'How we understand education quality is inextricably linked with perspectives on social justice. Questions of inclusion, relevance and democracy in education are increasingly contested, most especially in the global South, and improving the quality of education, particularly for the most disadvantaged, has become a topic of fundamental concern for education policy makers, practitioners and the international development community. The reality experienced by many learners continues to be of inadequately prepared and poorly motivated teachers, struggling to deliver a rapidly changing curriculum without sufficient support, and often using outmoded teaching methods in over-crowded or dilapidated classrooms. Education Quality and Social Justice in the South includes contributions from leading scholars in the field of education and development. The text draws upon state of the art evidence from the five year EdQual research programme, which focuses upon raising achievement in low income countries, and demonstrates how systems of high quality universal education can be sustained. The book is divided into three main parts: -Framing Education Quality -Planning and Policies for Quality -Implementing Quality in Schools Education Quality and Social Justice in the South argues that implementing a high quality of education using theories of social justice can inform the understanding of inclusion, relevance and democracy in education. The book should be essential reading for both students and researchers within the fields of international and comparative education, along with educational policy, poverty and development studies'--
Includes bibliographical references and index.
Keywords: Educational equalization -- Developing countries -- Cross-cultural studies; Educational sociology -- Developing countries -- Cross-cultural studies; Social justice -- Developing countries -- Cross-cultural studies